EFFECT OF SPACINGS AND FERTILITY LEVELS ON GROWTH, YIELD AND QUALITY OF COTTON (GOSSYPIUM HIRSUTUM L.) HYBRIDS UNDER RAINFED CONDITION OF VIDARBHA - U. N. SHUKLA; M. S. KHAKARE; V. K. SRIVASTAVA; KUMAR, RAKESH; SINGH, SMITA, V. KUMAR; K. KUMAR (The Bioscan, 2013)
Plants under closer spacing of 60 x 60cm (S2) produced significantly more LAI, seed cotton yield, crop profitability, crop productivity and PFPN over wider plant spacing (90 x 60cm), respectively, whereas 9.86% higher lint index was recorded under wider spacing. However, wider spacing produced significantly higher growth attributes viz. dry matter, CGR and RGR at 120 DAE and 150 DAE, respectively over closer spacing. Significantly higher dry matter (46.95 and 88.54 g/plant), CGR (0.468 and 1.386g/day/plant), RGR (0.016 and 0.028g/g/day/plant at120 DAE and 150 DAE, respectively), leaf area index, seed cotton yield, crop profitability and crop productivity was produced by MLCH-318 over VBCH-2231 and PKV Hy-2. Among fertility levels the significantly higher dry matter, CGR, RGR, LAI, seed index, seed cotton yield, crop profitability and crop productivity were produced under application of 62.50-31.25-31.25kg N-P2O5-K2O/ha (F3) over the rest of NPK levels, whereas lowest response to added nitrogen i.e. PFPN (15.55 kg/kg N) was obtained with highest level of nitrogen applied in F3 treatment. When hybrid MLCH-318 sown at closure spacing and fertilized with F3 (62.50-31.25-31.25 kg N-P2O5K2O/ha) recorded significantly higher moisture depletion, consumptive use and WUE.